So notice how the variable inside the parentheses after the function changes into a number (t changes to -10 and n changes into -6). This means to change every variable within the function into the number inside the parentheses that the variable turned into.
So, for m(-10) if m(t) = -(t + 6):
m(-10) = -((-10)+6)
Remember, flip the equation since it's a negative outside the parentheses.
m(-10) = (10 – 6); m(-10) = 4
Same for the second equation.
a(-6) if a(n) = 7 + n
a(-6) = 7 + (-6)
a(-6) = 7 – 6
a(-6) = 1
So these are your answers:
m(-10) = 4
a(-6) = 1